1963
DOI: 10.1126/science.140.3563.172
|View full text |Cite
|
Sign up to set email alerts
|

Altruism or Arousal in the Rat?

Abstract: If rats are exposed successively to white noise, then to recorded rat squeals, or alternatively to squeals first and then white noise, and if, in both situations, they are allowed to shut off the auditory stimulation by applying pressure on a bar, they will touch the bar more frequently when exposed to white noise. The results indicate that the bar-pressing behavior is the expression of increased activity resulting from the increased stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 1 publication
0
30
0
Order By: Relevance
“…Studies suggesting that rodents are attentive to and affected by the distress of a conspecific date back 50 years, when Church (1959) demonstrated that rats can be conditioned using the footshock of another rat as the unconditioned stimulus (also see Chen, Panksepp, & Lahvis, 2009). Soon after it was demonstrated that rats would perform operant responses to terminate the distress of a conspecific (Rice & Gainer, 1962), although this was dismissed as arousal rather than altruism (Lavery & Foley, 1963). A recent Pain Communication 60 series of experiments was performed using a "jail" paradigm, in which some mice in a dyadic or triadic interaction were free to move and others were constrained behind metal bars (Langford et al, 2010b).…”
Section: Pain Communication 57mentioning
confidence: 99%
“…Studies suggesting that rodents are attentive to and affected by the distress of a conspecific date back 50 years, when Church (1959) demonstrated that rats can be conditioned using the footshock of another rat as the unconditioned stimulus (also see Chen, Panksepp, & Lahvis, 2009). Soon after it was demonstrated that rats would perform operant responses to terminate the distress of a conspecific (Rice & Gainer, 1962), although this was dismissed as arousal rather than altruism (Lavery & Foley, 1963). A recent Pain Communication 60 series of experiments was performed using a "jail" paradigm, in which some mice in a dyadic or triadic interaction were free to move and others were constrained behind metal bars (Langford et al, 2010b).…”
Section: Pain Communication 57mentioning
confidence: 99%
“…Altruistic behavior in lower animals has been investigated by controlled experiment (Lavery & Foley, 1963;Massennan, Wechkin, & Terris, 1964;Rice & Gainer, 1962), but there are mixed conc1usions about the existence of such behavior and about its detenninants. The research described here was designed to establish more conclusively the presence or absence of altrilistic behavior in the white rat.…”
mentioning
confidence: 99%
“…In this group Os that had been shocked prior to the experiment showed altruistic behavior. Two existing hypotheses to account for altruistic behavior are: (a) that it is innate or "instinctive" (Masserman et al, 1964;Rice & Gainer, 1962); (b) that it serves merely to reduce the intensity of physical noxious stimuli (Lavery & Foley, 1963).…”
mentioning
confidence: 99%
“…This aiding behavior was termed "altruistic" by the authors. Lavery & Foley (1963) suggested that the Rice and Gainer results could be due to an increased activation effect due to arousal rather than to "altruism." In a follow-up study by Rice (1964), rats that were exposed to another rat being shocked did not press a bar to terminate the shock, and instead exhibited signs of fear.…”
Section: Discussionmentioning
confidence: 99%